Making space in the library: Considerations for design and furniture choices to support student wellbeing (Synergy, 2023)
Chin Ee Loh, Associate Professor and Deputy Head (Research) at the English Language and Literature Academic Group at the National Institute of Education of the Nanyang Technological University in Singapore, explores the ways the library space can support reading, student wellbeing and learning.